Rapid nitrogen and phosphorus homeostasis transformation in Eupatorium adenophorum during invasion. (22nd August 2019) - Wu, A‐P; Liu, L; Qi, L‐Y; Zhong, W; Liang, Y‐S; Chen, F‐L; He, F‐F; Wang, Y‐H
Summary: Exotic plants can compete well with native species because many invasive species are considered better nutrient users in both low‐ and high‐resource environments. However, whether invasive plants can outperform native plants at all stages of invasion is not very clear. We investigated the nitrogen (N), phosphorus (P) and N:P homeostasis of an invasive Eupatorium adenophorum and a co‐occurring native plant Artemisia argyi in an area across the five invasion stages of E. adenophorum . The N homeostasis ( H N ) of E. adenophorum was higher than that of A. argyi, whereas the P and N:P homeostasis ( H P and H N/P ) were higher for A. argyi . For E. adenophorum, H N decreased, but H P and H N /P increased with the invasion time. For A. argyi, H N /P increased, H P and H N remained stable with the invasion time. The results demonstrated that E. adenophorum could maintain higher H N during invasion stages when N was limited and could maintain higher H N and H P at invasion stages when P was more limited. This rapid nitrogen and phosphorus homeostasis transformation of invasive E. adenophorum during its invasion stages guarantees its stronger competitive ability over native species and promotes its invasion success.